KONTRIBUSI POWER LENGAN DAN FLEKSIBILITAS PINGGANG TERHADAP PRESTASI NOMOR KAYAK SLALOM ARUS DERAS CABANG OLAHRAGA DAYUNG - Indra Gerhana, - (2012)
This research is backgrounded to know how big contribution from power arm and waist flexibility and among both alatogethering to kayak slalom's number achievement pedal sporting branch race. It is infused one observational problem which is, what is power arms and positive waist flexibility to kayak slalom's number achievement pedal sporting branch race. Meanwhile aim of this research is subject to be know percentage to outgrow its contribution which given by power arm and waist flexibility to kayak slalom's number achievement pedal sporting branch race.Observational method that is utilized in this research is descriptive method, in this method writer takes population and sample of SME athlete row UPI. In its sample take writer utilizes purposive's tech sampling which its sample is kayak's athlete rows UPI as much 10 person. Observational instrument that is utilized is: 1 ) Tool measures power arm is ergo kayak. 2 ) Tool those are utilized to measure waist flexibility is Lucky meter. 3 ) meanwhile tools to measure achievements which is by essay to row at race,Processing result and analisis is data was gotten by correlation among power arm and kayak slalom's number achievement race is positive and give contribution as big as 40,96%, correlation among flexibility bursts sides and kayak slalom's number achievement pedal sporting branch race is positive and give contribution as big as 23,4%, and power is arm and waist flexibility with positive correlation and gives contribution as big as 42,25% to kayak slalom's number achievement pedal sporting branch races.From description already being interposed from analisis data upon hit power's correlation arm and waist flexibility to kayak slalom's number achievement pedal sporting branch race, therefore writer gleans from as follows: 1 ) available contribution which positives and signifikan among power arms with kayak slalom's number achievement race. 2 ) available contribution which positives but not signifikan among flexibility bursts sides with kayak slalom's number achievement race. 3 ) available contribution which positives but not signifikan among power arm and waist flexibility with kayak slalom's number achievement pedal sporting branch race.